Complement receptor CD46 co-stimulates optimal human CD8+ T cell effector function via fatty acid metabolism. Issue 1 (December 2018) - Arbore, Giuseppina; West, Erin; Rahman, Jubayer; Friec, Gaelle; Niyonzima, Nathalie; Pirooznia, Mehdi; Tunc, Ilker; Pavlidis, Polychronis; Powell, Nicholas; Li, Yuesheng; Liu, Poching; Servais, Aude; et al.
Abstract The induction of human CD4+ Th1 cells requires autocrine stimulation of the complement receptor CD46 in direct crosstalk with a CD4+ T cell-intrinsic NLRP3 inflammasome. However, it is unclear whether human cytotoxic CD8+ T cell (CTL) responses also rely on an intrinsic complement-inflammasome axis. Here we show, using CTLs from patients with CD46 deficiency or with constitutively-active NLRP3, that CD46 delivers co-stimulatory signals for optimal CTL activity by augmenting nutrient-influx and fatty acid synthesis. Surprisingly, although CTLs express NLRP3, a canonical NLRP3 inflammasome is not required for normal human CTL activity, as CTLs from patients with hyperactive NLRP3 activity function normally. These findings establish autocrine complement and CD46 activity as integral components of normal human CTL biology, and, since CD46 is only present in humans, emphasize the divergent roles of innate immune sensors between mice and men. Complement, while serving to remove pathogens in the circulation, is also important for synergizing with inflammasomes to modulate CD4 T cell activation. Here the authors show that CD46, a complement receptor expressed only in humans, is essential for inducing optimal activation and effector functions of human CD8 T cells.